Thoracentesis in advanced cancer patients with severe thrombocytopenia: Ultrasound guide improves safety and reduces bleeding risk. (12th December 2017) - Orlandi, Elena; Citterio, Chiara; Seghini, Pietro; Di Nunzio, Camilla; Mordenti, Patrizia; Cavanna, Luigi
Abstract: Background: Patients with severe thrombocytopenia are considered at risk for bleeding during invasive procedures as thoracentesis. The use of ultrasound (US) significantly reduces the rate of pneumothorax from thoracentesis, but there is a lack of data on safety and efficacy of US guidance in reducing bleeding complications in thoracentesis performed on patients with severe thrombocytopenia. Methods: We retrospectively analysed the efficacy and safety of thoracentesis in cancer patients with severe thrombocytopenia. From January 2005 to December 2011, 462 patients underwent thoracentesis. Procedures were divided into 2 groups: performed without or with US guidance. All procedures were evaluated for bleeding complications as defined by the National Institutes of Health Common Terminology Criteria for Adverse Events. Results: A total of 436 consecutive evaluable thoracentesis were analysed. Thoracentesis was performed with US guidance in 310 cases. Forty‐one patients (9.40%) had severe thrombocytopenia. In 32 of these 41 patients, thoracentesis was performed under US guidance while in 9 cases the procedure was performed without US guidance. Three mild haemorrhagic complications (0.69% of the procedures performed) were observed and all occurred in group of the 9 (33.33%) patients with severe thrombocytopenia who underwent thoracentesis without US guidance. No haemorrhagic complications were recorded in the 427 patients, including the 32 patients with severe thrombocytopenia, in whom thoracentesis was performed with US guidance. Conclusions: US guided thoracentesis is a safe and effective approach in cancer patients with severe thrombocytopenia. Our results indicate that this procedure, when US‐guided, can be safety performed even in patients with platelet count below 30 × 10 9 /L.